Pengaruh Pendekatan RME terhadap Hasil Belajar Matematika - Muncarno Muncarno; Nelly Astuti (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
The problem in this research is the low of mathematics learning result of grade V student of SD Negeri 6 Metro Utara. The purpose of this research was to know the influence of realistic mathematics education (RME) approach to the result of V grade student mathematics. The type of the research was experiment research. The design used in this research was quasi experimental design. Population research is all of students V grade, the sample consists 26 students VA class and 27 student VB class. The determination of research sample used purposive sample. Data collection tools used questionnaires and cognitive tests. The data analysis was used t-test pooled varians. The learning results of this research was limited only to the cognitive domain. The result showed that there was a significant influence on the application of realistic mathematics education (RME) approach to the students' mathematics learning outcomes.